Female work status and child nutritional outcome in Nigeria - Rama Lionel Ngenzebuke; Yoko Akachi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper delves into the relationship between child nutritional outcome and (multiple) female work status in Nigeria from a micro perspective. The child nutritional outcome is proxied by child weight-for-age. Female work includes wage employment outside the household, household on-farm agricultural work, and household non-farm enterprise activities. Multilevel mixed-effects regression results show that female involvement in any type of work is positively and significantly associated with child weight-for-age. However, female simultaneous involvement in on-farm and non-farm work is the only female work combination positively and significantly associated with child weight-for-age. We describe the mechanism behind our findings through the lens of (positive) income effect versus (negative) childcare effect, which is consistent with two sets of further findings. On one hand, sub-sample analysis shows that female wage work significantly matters, in a non-linear fashion, for children aged two to five years (toddlers) and boys exclusively. On the other hand, female on-farm work significantly matters for children aged zero to two years (infants) and girls exclusively.
Keywords: J2; J3; I3; 330; female work status; income effect; childcare effect; child nutrition; Nigeria